2012
DOI: 10.1016/j.diii.2011.12.008
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of indirect ultrasound signs during acute adult appendicitis

Abstract: When tomodensitometry cannot be performed and the appendix is not visible on ultrasound examination, indirect ultrasound signs must be systematically sought, particularly in populations in which appendicitis are highly prevalent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…US Pelvis. Three retrospective studies of pelvic US were identified with one single-institution study combining transabdominal and transvaginal imaging in 292 women [46] and two multi-institutional studies [47,48] evaluating 573 and 620 male and female patients with iliac fossa US, respectively. Greatest sensitivity of 97.3%, specificity of 91.0%, PPV of 91.7%, and NPV of 97% were achieved when combining transabdominal US and transvaginal US performed by a single experienced operator in adult women (95% CI).…”
Section: Discussion Of Procedures By Variantmentioning
confidence: 99%
See 3 more Smart Citations
“…US Pelvis. Three retrospective studies of pelvic US were identified with one single-institution study combining transabdominal and transvaginal imaging in 292 women [46] and two multi-institutional studies [47,48] evaluating 573 and 620 male and female patients with iliac fossa US, respectively. Greatest sensitivity of 97.3%, specificity of 91.0%, PPV of 91.7%, and NPV of 97% were achieved when combining transabdominal US and transvaginal US performed by a single experienced operator in adult women (95% CI).…”
Section: Discussion Of Procedures By Variantmentioning
confidence: 99%
“…Greatest sensitivity of 97.3%, specificity of 91.0%, PPV of 91.7%, and NPV of 97% were achieved when combining transabdominal US and transvaginal US performed by a single experienced operator in adult women (95% CI). Nonvisualization of the appendix ranged from 20.3% [48] to 45% [47]. There is wide variability with ranges of sensitivity of 31.8% to 83.9%, specificity of 56.7% to 96.7%, PPV of 25% to 95.8%, and NPV of 57.2% to 83.3% related to presence and combination of clinical and US signs of appendicitis that include pain, hypertrophic fat, and diminished peristalsis [48].…”
Section: Discussion Of Procedures By Variantmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study showed that absence of transducer tenderness in the RLQ and hypertrophy of the peritoneal fat has a NPV of only 66%. 33 Therefore, US only seems not suitable to exclude appendicitis in patients who have strong clinical suspicion of appendicitis based on clinical signs and symptoms.…”
Section: Discussionmentioning
confidence: 99%